Properties of soils in different agricultural uses, Las Tunas, Cuba - Leyva R., Santa Laura; Baldoquín P., Aime; Reyes O., Manuel (Revista de Ciencias Agrícolas, 2018)
The degradation of pastures, constitutes one of the most serious problems related to the use of soils in the northern area of Las Tunas municipality, Cuba. The inadequate management of soils, has led to their progressive deterioration with negative impacts on livestock, which has affected the production of meat and milk, increases of production costs and adverse effects on the environment. In the present work, the effect of different agricultural systems on some properties of haplic Luvisoles soils, developed on granitoids, was evaluated. The systems included natural pastures, cultivated pastures, silvopastoral system and a natural system. The soil properties evaluated were texture, bulk density, field capacity, total porosity and aeration, infiltration speed, organic matter and β-glucosidase enzyme. The management technologies applied in the grasslands affect the soil properties and their degradation, with increases in the apparent density, lower values of infiltration, porosity and lower activity of the enzyme ß-glucosidase, which limits the functioning of the soil-plant-animal system. It was evident a preserving effect of the soils in the silvopastoral system regarding to the physical, the chemical and the biological properties, which indicates that they are alternatives for the recovery of grassland soils in the cattle systems.